Antibiofilm Activity, Compound Characterization, and Acute Toxicity of Extract from a Novel Bacterial Species of Paenibacillus - Alasil, S.M.; Omar, R.; Ismail, S.; Yusof, M.Y. (Hindawi Publishing Corporation, 2014)
The effectiveness of many antimicrobial agents is currently decreasing; therefore, it is important to search for alternative therapeutics. Our study was carried out to assess the in vitro antibiofilm activity using microtiter plate assay, to characterize the bioactive compounds using Ultra Performance Liquid Chromatography-Diode Array Detection and Liquid Chromatography-Mass Spectrometry and to test the oral acute toxicity on Sprague Dawley rats of extract derived from a novel bacterial species of Paenibacillus strain 139SI. Our results indicate that the crude extract and its three identified compounds exhibit strong antibiofilm activity against a broad range of clinically important pathogens. Three potential compounds were identified including an amino acid antibiotic C8H20N3O4P (MW 253.237), phospholipase A2 inhibitor C21H36O5 (MW 368.512), and an antibacterial agent C14H11N3O2 (MW 253.260). The acute toxicity test indicates that the mortality rate among all rats was low and that the biochemical parameters, hematological profile, and histopathology examination of liver and kidneys showed no significant differences between experimental groups . Overall, our findings suggest that the extract and its purified compounds derived from novel Paenibacillus sp. are nontoxic exhibiting strong antibiofilm activity against Gram-positive and Gram-negative pathogens that can be useful towards new therapeutic management of biofilm-associated infections.